A Science Mapping Analysis of Energy Efficiency and Affordable Housing Research - Adediran, Anthonia Oluwatosin; Ajibade, Samuel-Soma; Zaidi, Abdelhamid; Bashir, Faizah Mohammed; Falude, Emmanuel; Dodo, Yakubu Aminu; Jasser, Muhammed Basheer (International Journal of Energy Economics and Policy, 2024)
The research landscape on energy efficiency and affordable housing research (EE-AHR) was critically examined through bibliometric analysis and a literature review of Scopus-indexed publications from 2001 to 2023. Results showed that the total publications and total citations on AH are 630 documents and 4,347 citations. Document type distribution revealed articles (75.7%), conference proceedings (19.8%), and reviews (4.4%). The observably high EE-AHR metrics are attributed to stakeholders’ productivity, funding, and collaborations among other various authors, affiliations, and countries strategically involved in EE-AHR. The most prolific authors are Gurran, N. and Milligan, V., whereas UNSW Sydney is the most productive affiliation. Likewise, the most productive country is the United States, whereas China’s National Natural Science Foundation is EE-AHR’s most active funder. Social network analysis revealed that collaboration, particularly between affiliations, was critical to productivity in the EE-AHR landscape. Keywords co-occurrence identified Energy, Efficiency, Affordable Housing, Housing, and Housing Policy as the 3 top keywords. In contrast, Housing Sector Dynamics, Sustainable Housing Development, and Urban Development Planning are thematic research areas on AHR. Systemic literature review revealed that EE-AHR is multidisciplinary and impactful, particularly as it seeks to build secure, resilient, inclusive, and sustainable human settlements and cities as per the UN SDGs Goal 11. As such, it has significant potential for future research, collaboration, and growth. Nonetheless, critical research gaps (e.g., examining globalized application techniques, social outcomes, and organizational frameworks) in EE-AHR must be tackled comprehensively. Future research will also need to explore technology applications, innovative materials, social integration, environmental sustainability, and net-zero carbon goals applicable to AH.